Problematic theatrical landscape design Between the director and designer (Al-Academy, 2024)
This research discussed analytically based on intellectual institutions and theoretical landscape theater as artistic phenomenon depends on the compounds interacting overlapping mechanism visualization and dazzling Whatever the dilemma it a set of Alaqcar differ among themselves but in the result unit intellectual holds through difference and diversity between trends and styles and ways in design theorist theatrics Valashkalah on apparently formed through variations and different points of view through the philosophy of transformation and interpretation and assignment to offer privacy.Valashkalah pulled in the design theorist theatrical as system training to arrange time and place and in line with the interpretation of speech text and this is linked to awareness - when the designer - and director through Zhnihm and see shapes and configurations through contradiction or agreement for that has divided the researcher discussed into four chapters.Chapter One - systematic framework which guarantees the research problem and its importance and the need for him and his goals, limitations and concluded the following chapter defines terminology (the dilemma - theatrical theorist).Chapter II - has contained a theoretical framework for research and previous studies, including the three sections:1 - The first topic: the theatrical scene.2 - The second topic: theatrical scene in the Iraqi theater (historical perspective).3 - The third topic: theatrical scene between problematic director and designer.The chapter concluded indices to which each theoretical framework.The third chapter - has included research and procedures that will be from the research community, which was limited to the Iraqi theater either sample was the research community is the same sample